Maksimalisasi fluks netron cepat pada posisi irradiasi pusat (cip) reactor g.a. siwabessy - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1998)
. Changes of configuration and composition of CI? (Central Irradiation Position) in G.A. Siwabessy (RSG-GAS) reactor have been investigated in order to maximize the fast neutron flux in the CIP to support the sample irradiation program in the reactor. The flux distribution as a function of neutron energy was obtained by solving multigroup neutron diffusion equation. The multigroup parameters were generated by WIMS/D4 code. The solution of the neutron multigroup diffusion equation was undertaken by UM2DB code using the VAX mainframe computer of BATAN, Serpong. Normally with water in the CIP, a fast neutron flux of 3.84.10" n/ cm2-s is obtained and the ratio with respect to the thermal neutron flux is 23.7. Of all the configurations and compositions for CIP tested a very high ratio of fast to thermal neutron flux is obtained (10') when the CIP was filled with oxygen gas. The ratio also increases (from 3.72 % to 14.4 %) when the CIP wall was coated with neutron absorbing materials like Cadmium, Argentum, and Gadolinium. The maximum increase in absolute fast netron flux occurs when the CIP was filled with oxygen gas (3.91 %), uranium solution in water (0.26 %), or the CIP wall coated with uranium (0.26 %)